2015
DOI: 10.1371/journal.pone.0122797
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Loci Associated with Gastrointestinal Parasite Resistance in a Red Maasai x Dorper Backcross Population

Abstract: Gastrointestinal (GI) parasitic infection is the main health constraint for small ruminant production, causing loss of weight and/or death. Red Maasai sheep have adapted to a tropical environment where extreme parasite exposure is a constant, especially with highly pathogenic Haemonchus contortus. This breed has been reported to be resistant to gastrointestinal parasite infection, hence it is considered an invaluable resource to study associations between host genetics and resistance. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 65 publications
(65 reference statements)
5
69
0
2
Order By: Relevance
“…A raça Dorper apresenta alta taxa de desenvolvimento de carcaça com boa conformação, sendo muito utilizada em cruzamentos com ovelhas de raças nativas do Nordeste, tais como a Santa Inês, em virtude do seu porte e da velocidade de crescimento (Carneiro et al 2007). Também já foi descrito que características genéticas da raça Dorper conferem maior resistência a parasitos gastrointestinais (Benavides et al 2015), o que torna essa raça de alto interesse para criação em regiões brasileiras caracterizadas por alta infestação com esses parasitos (Wilmsen et al 2014). Com o objetivo de aumentar a produção de carne ovina, aumentou-se o interesse no monitoramento da sanidade do rebanho, utilizando diversas ferramentas como auxiliares no diagnóstico clínico, tais como os intervalos de referência para metabólitos sanguíneos (componentes hemato-bioquímicos) (Peixoto & Osório 2007).…”
Section: Introductionunclassified
“…A raça Dorper apresenta alta taxa de desenvolvimento de carcaça com boa conformação, sendo muito utilizada em cruzamentos com ovelhas de raças nativas do Nordeste, tais como a Santa Inês, em virtude do seu porte e da velocidade de crescimento (Carneiro et al 2007). Também já foi descrito que características genéticas da raça Dorper conferem maior resistência a parasitos gastrointestinais (Benavides et al 2015), o que torna essa raça de alto interesse para criação em regiões brasileiras caracterizadas por alta infestação com esses parasitos (Wilmsen et al 2014). Com o objetivo de aumentar a produção de carne ovina, aumentou-se o interesse no monitoramento da sanidade do rebanho, utilizando diversas ferramentas como auxiliares no diagnóstico clínico, tais como os intervalos de referência para metabólitos sanguíneos (componentes hemato-bioquímicos) (Peixoto & Osório 2007).…”
Section: Introductionunclassified
“…Resistance to GINs, like many complex traits, is influenced by many genes and a large proportion cannot be captured using the technologies or sample sizes currently employed in much of the research in this area. Studies which used the Ovine50SNP chip reported that less than 0.5% of the SNP markers were significantly associated with FEC and that, in the case of the most significant effects, there was no known gene in the region . While there is little evidence of any major selective sweeps in the sheep populations studied to date, selection under a polygenic‐control model would result in modest allele frequency changes across the genome, which may be undetectable using current methods, which seems to fit with the current genetic evidence on parasite resistance in ruminants.…”
Section: Genetic/genomic Markers Of Resistance To Gin Infectionmentioning
confidence: 55%
“…Hence, both Kemper et al . and Benavides et al . are consistent in finding that <5% of the phenotypic variance in FEC arising from H. contortus infection can be accounted for by observed variation in SNP genotype.…”
Section: Genetic/genomic Markers Of Resistance To Gin Infectionmentioning
confidence: 61%
See 2 more Smart Citations